The Implementation Gap of Food Security Policy : A Structural Analysis of Extractive Dominance and Agrarian Politics - Yacob Yacob; Paisal Akbar; Niken Nurmiyati; Reksa Burhan (Universitas Muhammadiyah Ponorogo, 2027)
Food security in Indonesia faces a paradox between regulatory commitments and the reality of agrarian politics, especially in extractive regions. This study analyzes the root causes of the failure to implement food security policies in West Kutai Regency, East Kalimantan, an area with a drastically declining Food Security Index (FSI) despite its large agricultural land potential. Using a qualitative approach and document analysis of regional regulations as well as spatial and statistical secondary data, this study reveals three interrelated layers of problems. First, the land tenure structure dominated by Other Use Areas (APL) and the political licensing cycle have narrowed the space for food policy from the outset. Second, policy contradictions arise when food diversification programs have to compete with much greater incentives and licensing facilities for the palm oil and coal mining sectors. Third, the adaptive Sustainable Food Gardens (P2L) program emerged as a survival strategy at the household level, but its effectiveness is limited and risks becoming a symbolic compensation for the loss of large-scale food barns. This study concludes that the implementation gap in West Kutai is structural and political in nature, caused by the subordination of the food agenda to the extractive development regime. The policy implications demand coherent integration between food planning, spatial planning, and extractive sector regulation, as well as legal protection for sustainable agricultural areas.